2020
DOI: 10.1155/2020/1749351
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Real-Time Tissue Elastography Improves the Diagnostic Performance of the ACR Thyroid Imaging Reporting and Data System in Differentiating Malignant from Benign Thyroid Nodules: A Summary of 1525 Thyroid Nodules

Abstract: Background. To explore the correlation between the ultrasound elasticity score (ES) of real-time tissue elastography (RTE) and the malignant risk stratification of the Thyroid Imaging Reporting and Data System (TI-RADS) and to evaluate the added value of RTE to TI-RADS in differentiating malignant nodules from benign ones. Methods. A total of 1,498 patients (885 women and 613 men; mean age of 43.5 ± 12.4 years) with 1,525 confirmed thyroid nodules (D = maximum diameter, D ≤ 2.5 cm) confirmed by fine-needle asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 43 publications
4
9
0
5
Order By: Relevance
“…This meta-analysis uncovered that RTE had greater diagnostic value than SWE in distinguishing malignant from benign nodules ( 32 ). Furthermore, the ES of RTE was intensely associated with the malignant risk stratification of TI-RADS ( 33 ). Some researches applied SWE to forecast CLNM in PTC patients, the results demonstrated that SWE can improve the performance for preoperative lymph node staging ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…This meta-analysis uncovered that RTE had greater diagnostic value than SWE in distinguishing malignant from benign nodules ( 32 ). Furthermore, the ES of RTE was intensely associated with the malignant risk stratification of TI-RADS ( 33 ). Some researches applied SWE to forecast CLNM in PTC patients, the results demonstrated that SWE can improve the performance for preoperative lymph node staging ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“… 12 Furthermore, the addition of RTE had been shown to improve the diagnostic accuracy of TI-RADS. 22 In suspected prostate cancer, RTE has been found to be useful in combination with Prostate Cancer Gene 3 (PCG3) scores as a pre-biopsy diagnostic indicator to reduce the number of prostate biopsies. 23 In addition, RTE in combination with magnetic resonance imaging (MRI) has been found to increase precision of localizing prostate cancer lesions compared with MRI alone.…”
Section: Discussionmentioning
confidence: 99%
“…Однако трансректальное ультразвуковое исследование не является высокочувствительным или специфичным для диагностики РПЖ [7]. Между тем цветная и энергетическая допплеровская визуализация существенно не улучшают диагностическую точность [8]. Лишь патологический результат, полученный при трансректальной УЗИ-биопсии, остается основой подтверждения PПЖ [3].…”
Section: наилучшее значение порогового значенияunclassified
“…Прогрессия и летальность при Глисон 6 были намного ниже, чем Глисон ≥7 [35,36]. В некоторых исследованиях [3,8,11,17] сообщалось, что частота выявления рака предстательной железы с более высокой оценкой по шкале Глисона была выше, чем при низких значений по шкале Глисона. В настоящем исследовании не было никаких существенных различий между средними показателями для Глисона <7 и таковыми для Глисона ≥7.…”
Section: наилучшее значение порогового значенияunclassified
See 1 more Smart Citation